2020
DOI: 10.1136/bjophthalmol-2020-317848
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of topical polyhexamethylene biguanide: a randomised clinical trial in healthy adult volunteers

Abstract: Background and AimsPolyhexamethyl biguanide (PHMB), a widely used topical treatment for Acanthamoeba keratitis (AK), is unlicensed with no formal safety assessment. This study evaluated its safety and tolerability.MethodsA prospective, randomised, double-masked controlled trial in 90 healthy volunteers. Subjects were treated with topical 0.04%, 0.06%, 0.08% PHMB or placebo (vehicle) 12× daily for 7 days, then 6× daily for 7 days. The rates of dose-limiting adverse events (DLAEs) leading to interruption of dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Weekly and monthly contact lens wearers are required to disinfect their lenses daily, and due to a variety of risk factors, including poor hand hygiene and the choice of MPS, are at risk of infection. AK which is caused by Acanthamoeba is of particular concern, as it is able to form a highly resistant cyst that is resistant to disinfection [ 12 ], and when a patient contracts AK, it requires a protracted treatment regime with a mean treatment time of many moths to effect a cure [ 10 ]. Therefore, there is an urgent need to identify alternative compounds for the inclusion into MPS for contact lens disinfection and for the treatment of AK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weekly and monthly contact lens wearers are required to disinfect their lenses daily, and due to a variety of risk factors, including poor hand hygiene and the choice of MPS, are at risk of infection. AK which is caused by Acanthamoeba is of particular concern, as it is able to form a highly resistant cyst that is resistant to disinfection [ 12 ], and when a patient contracts AK, it requires a protracted treatment regime with a mean treatment time of many moths to effect a cure [ 10 ]. Therefore, there is an urgent need to identify alternative compounds for the inclusion into MPS for contact lens disinfection and for the treatment of AK.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its use in commercial MPS, PHMB is also widely used topically in the treatment of Acanthamoeba keratitis (AK) [ 10 ]. Current first-line medical therapy for AK is unlicensed and usually involves a biguanide, which is either chlorhexidine or PHMB as a monotherapy at 0.02% ( v / v ) or in combination with 0.1% ( v / v ) propamidine or 0.1% hexamidine ( v / v ), all administered as eye drops several times per day [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this has not prevented clinical use suggesting that these laboratory findings are less relevant in vivo. Polyhexanide drops have been used to treat ophthalmic infections, and one phase I trial has demonstrated no dose-limiting adverse effects when used at a concentration of 0.04% ( Papa et al, 2020 ). Nasal epithelial ciliary beating is markedly slowed on exposure to concentrations as low as 0.01%, however, with complete and relatively swift ciliostasis seen at higher concentrations within the clinical dosage range ( Birk et al, 2015 ).…”
Section: Biguanidesmentioning
confidence: 99%
“…is susceptible to multiple therapies, the cystic form is highly drug resistant and may persist for months [8]. The principal initial treatment is the administration of a topical biguanide, such as polyhexamethylene biguanide (PHMB) 0.02-0.08% [37] or chlorhexidine 0.02-0.06% [38], along with or without a topical diamidine, such as propamidine isethionate 0.1% [2][3][4][6][7][8]11,12,20,21,27]. Initially, these medications should be administered every hour around the clock for the first 48-72 h and then tapered gradually.…”
Section: Treatmentmentioning
confidence: 99%